A Just (Electric Lady) Land: Jimi Hendrix and John Rawls. Issue 3 (2nd September 2017) - Sykes, Robbie; Tranter, Kieran
Abstract: This article argues that the life and work of rock musician Jimi Hendrix reveals that John Rawls's A Theory of Justice is politically inert. Rawls sought to convince of the principles needed for a just society via an abstract scenario of his own making. Comparably, Hendrix attempted to free the minds of his listeners by depicting, through his surreal lyrics and prismatic guitar playing, mental journeys to elevated states of awareness. Hendrix's depictions of ineffable internal states elucidate the difficulties of utilizing the abstract to improve real-world justice. The psychedelic "trips" on which Hendrix takes his listeners parallel the hallucinatory nature of Rawls's vision: the divestment of identity demanded by Rawls's logic alienates his plan for society from the imperatives of life in the political world.